CLINICAL SIMULATION IN NURSING PROFESSIONALS’ LATE RETENTION OF KNOWLEDGE AND SELFCONFIDENCE: A QUASI-EXPERIMENTAL STUDY - Araújo, Paula Roberta Silva; Santana, Breno de Sousa; Nogueira, Jane Walkíria da Silva; Magro, Marcia Cristina da Silva (Cogitare Enfermagem, 2022)
Objective: to evaluate the late effect of using combined simulation of a dialog lecture class, as compared to the exclusive use of simulation, on Nursing professionals’ self-confidence and knowledge under cardiopulmonary arrest situations. Method: quasi-experimental with pre- and post-test. Convenience sample comprised by 53 Nursing professionals divided into control and experimental groups. A semi-structured questionnaire and the Self-confidence dimension of the Satisfaction and Self-Confidence in Learning Scale were applied. Q tests were used with p-value≤ 0.05. Results: self-confidence increased significantly among the professionals from the experimental group (p=0.007) in relation to the control group (p=0.06). None of the groups showed significant gains in retained knowledge over time. Conclusion: regardless of how the simulation method is employed, it represents a pedagogical strategy that can enable the development and improvement of self-confidence and late knowledge fixation in relation to cardiopulmonary arrest situations.